Comparison of Contact Pressures Between Partial and Complete Femoral Osteoplasty Treatment in Hips with CAM Impingement. Issue 7 (31st July 2020) - Suppauksorn, Sunikom; Beck, Edward; Cancienne, Jourdan; Shewman, Elizabeth; Chahla, Jorge; Krivicich, Laura; Nho, Shane; Rasio, Jonathan
Objectives: To determine hip biomechanical properties in three conditions including 1) native cam deformity 2) cam deformity with incomplete resection and 3) cam deformity with complete resection. Methods: A cadaveric study was performed using 8 frozen hemi-pelvises with cam-type deformity (alpha angle >55 degrees) with an intact labrum. Intraarticular pressure maps were produced for each specimen under the following conditions: 1) native cam deformity, 2) cam deformity with incomplete resection and 3) cam deformity with complete resection. A 5.5-mm burr was used to resect the lateral portion of the cam deformity. The specimen was placed in a custom-designed jig in the MTS electromechanical test system to create pressure and area map measurements. In each condition, contact pressure, contact area, and peak force within a region-of-interest (ROI) were obtained. Repeated measurements were performed three times in each condition and the average value of each parameter was used for statistical analysis. Repeated measures ANOVA was used to compare biomechanical parameters between three conditions. Results: Contact pressures averages of hips with complete resection of cam lesions were significantly lower when compared to averages of hips with incomplete femoral cam lesion and intact cam deformity (2.48+0.56 kg/cm3 vs 2.32+0.50 kg/cm3 vs 2.02+0.54 kg/cm3, respectively; p-value<0.01). Percentage reduction of contact pressure in the complete and incomplete resection groups compared to the native CAM deformity groups were 18.49% and 1.58%, respectively. There was no statistically significant difference in contact pressures between the incomplete resection and unoperated group. Contact area and peak force showed no statistically significant differences across three conditions. Conclusion: There are lower intraarticular hip contract pressures in complete resection of the cam lesions when compared to an incomplete resection and intact hip without resection. These observations underscore the importance of ensuring complete resection of femoral cam lesions in patients undergoing hip arthroscopy for femoroacetabular impingement syndrome. Table 1. Biomechanical Contact Pressures of Intact CAM Deformity, Incomplete, and Complete CAM Resection Intact Cam Deformity Incomplete Resection Complete Resection p-value Contact Area (mm2) 15.94±2.15 15.92±2.24 15.84±2.18 0.220 % 100% 99.78% 99.35% Contact Pressure (kg/cm3) 2.48±0.56 2.32±0.50 2.02±0.54 0.010 % 100% 98.4% 81.5% Peak Force 14.82±2.56 15.11±2.80 14.34±2.62 0.882 % 100% 107.1% 101.6%